The Effectiveness of Educational Environment Based on Smart Learning in Developing English Language Speaking Skill among IUG Female Student - د/ مجدي سعيد عقل; د/ أحمد إسعيفان الصوراني (Taez University, 2022)
This study aimed to investigate the effectiveness of educational environment based on smart learning in developing English Language speaking skill among IUG female students. To achieve this aim, the researcher adopted the quasi-experimental approach. The study was applied on a representative sample of (30) female students of journalism and media second-level at the Islamic University of Gaza, and that is in the second semester of the academic year (2020-2021). In order to collect data, the researcher used one main tool, a pre- and post-speaking test, and then he verified the validity and reliability of the test. Results of the study revealed that There were significant statistically difference at level (0.05) between the average scores of female students in journalism and media at the Islamic University in the pre and post applications to test skill of speaking in English language and in favor of the post application. Based on upon the previous findings, the study recommended the necessity of implementing smart learning in teaching and learning English speaking skill to bring about better outcomes in female students' achievement. Also, the researcher suggested that further research should be conducted concerning the effectiveness of educational environment based on smart learning in teaching different English language skills.